Discrete Event Simulation Implementation for Service Throughput Optimization at Cafe King Kuphi - Dodyk Fahlome; M. Khalil Gibran; Akmal Baihaqi; Ikhwan Prananta Hasugian (G-Tech: Jurnal Teknologi Terapan, 2026)
King Kuphi Cafe has seen an increase in customers, especially during peak hours. As a result, long queues, long waiting times, and poor service have become problems. The purpose of this study is to evaluate and improve the performance of the ordering and serving process using the Discrete Event Simulation (DES) approach. This method is used to model a service system that includes customer arrival, ordering, preparation, and product serving. The data collected includes customer arrival time, service time at the cashier, beverage and food preparation time, and the number of available resources. According to the baseline simulation model, there were constraints in the ordering and preparation processes. This resulted in low throughput and long customer wait times. Subsequently, improvement scenarios such as adding staff, dividing service tasks, and adjusting workflows were tested. The simulation results showed that the optimal scenario could reduce wait times and increase service throughput compared to the baseline. Discrete Event Simulation has proven to help King Kuphi Cafe assess and improve its operational process performance. This research can be used as a basis for strategic decisions regarding resource management and service improvement in the culinary industry.